Analisi della persistenza e delle risorse allocate nel trattamento farmacologico dell’ipertensione arteriosa - Degli Esposti, Luca; Capone, Alessandro; Degli Esposti, Ezio; Valpiani, Giorgio; Di Martino, Mirko; Baio, Gianluca; Russo, Pierluigi; Buda, Stefano; Sturani, Alessandra; Caprino, Luciano (Farmeconomia. Health economics and therapeutic pathways, 2002)
In this study, the persistence with treatment and resources allocated in antihypertensive pharmacotherapy has been evaluated. Administrative databases of the Local Health Unit of Ravenna listing patients baseline characteristics, drug prescriptions and hospital admissions were used to perform a population-based retrospective study. All new users 20 years old or over receiving a first prescription for diuretics, beta-blockers, calcium channel-blockers, ACE inhibitors or AII-Antagonists between January 1st, 1997 and December 31st, 1997 were included. A one-year follow-up for prescriptions of anti-hypertensive drugs were considered. According to duration of therapy, treated population was divided in persistent patients (continuers and switchers) and non-persistent patients. A total of 16,783 patients was included in the study of whom 64.9% were non-persistents. Persistence with treatment seems to be associated with the class of anti-hypertensive drug initially prescribed, and with patient-related factors. Patients initially prescribed for AII-Antagonists were more likely to persist than those starting on the other antihypertensive classes. Annual antihypertensive treatment cost accounted for • 1,076,053.55 of which 25.4% for non-persistent patients. An appropriate use of claims data may be considered as a powerful tool, providing detailed epidemiological and economic information concerning the antihypertensive treatment.